Treatment of Super-Refractory Status Epilepticus - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Researchers at University College, Queen Square, London, UK have evaluated the world literature on the treatment of super-refractory status epilepticus (SRSE) and proposed a protocol and flowchart for management.